RELATIONSHIP BETWEEN PARTICIPATORY ADMINISTRATION AND EFFECTIVENESS OF SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Nurat , Wissanee; Thummarpon , Wirat (Journal of MCU Nakhondhat, 2023)
This study aims to 1) Investigate the participatory administration of school under Nakhon Si Thammarat Primary Education Service Area Office 2 2) The effectiveness of school under Nakhon Si Thammarat Primary Education Service Area Office 2 3) The relationship between participatory administration and effectiveness of school of school under Nakhon Si Thammarat Primary Education Service Area Office 2 4) Examine problems and suggestions concerning participatory administration of school administrators of school under Nakhon Si Thammarat Primary Education Service Area Office 2. This research used quantitative research. The study sample consisted of 128 schools under Nakhon Si Thammarat Primary Educational Service Area Office 2 whose sample size was based on Yamane’s formula with 95% confidence, and informants were vice school directors or heads of academic affairs. The instrument was a five-point rating scale. The data were analyzed to find the percentage, standard deviation, Pearson’s correlation coefficient, and t-test. The results revealed that 1) the overall and every aspect of participatory administration of school administrators was found at a good level ( = 4.34), in order from most to least, including trust, autonomy, organizational commitment, and goal setting. 2) The overall and every aspect of effectiveness of schools was found at a good level ( = 4.35) including organizational change and development, student learning achievement, developing students’ positive attitude, problem solving within schools. 3) There was a high level of relationship between the participatory administration and the effectiveness of schools (r=.628, r2=.394) at the significance level of .001. 4) The participatory administration problems indicated that school personnel lacked confidence of job performance, decision making when problems occurred, and administrators did not provide clarity on missions and quick policies. Suggestions were made that administrators should promote personnel training on their assign tasks, create employee performance manual, and build understanding on quick policies among personnel.